Non-targeted screening and characterization of organic pollutants in wastewater from an industrial park in China - Xu Tan; Shanwei Sun; Song Hou; Linlin Wu; Yangwei Bai; Hongbo Xi; Jian Xu; Changsheng Guo (Emerging Contaminants)
Industrial parks are significant sources of complex water pollution, making it challenging to trace pollutant origins and ensure water quality. This study established a non-targeted screening workflow and compound persistence, mobility, and toxicity (PMT) assessment method to identify and characterize organic pollutants in wastewater from a chemical industrial park in Central China. Among the 255 compounds identified, some aromatic ketones and phthalate esters raised concerns due to their potential health effects. PMT assessment revealed 2 PMT/vPMT (v = very) compounds, 36 potential PMT/vPMT compounds, and 50 potential PT/vPT or PM/vPM compounds. Exposure-discharge modeling indicated the wastewater treatment plant's limited efficiency in treating the predominantly aromatic pollutants. Traceability analysis identified 23 characteristic pollutants from eight enterprises. This study provides valuable insights for identifying unknown compounds, evaluating industrial wastewater discharge standards, and enabling precise management of water pollution in industrial parks.